Lulo cell line derived from Lutzomyia longipalpis (Diptera: Psychodidae) : A novel model to assay Leishmania spp. and vector interaction (2011)
Background: Leishmania (Vianna) braziliensis, Leishmania (Leishmania) amazonensis and Leishmania (Leishmania) chagasi are important parasites in the scenario of leishmaniasis in Brazil. During the life cycle of these parasites, the promastigote forms adhere to the midgut epithelial microvillii of phlebotomine insects to avoid being secreted along with digestive products. Lulo cells are a potential model that will help to understand the features of this adhesion phenomenon. Here, we analyze the interaction between Leishmania spp. promastigotes and Lulo cells in vitro, specifically focusing on adhesion events occurring between three Leishmania species and this cell line. Methods. Confluent monolayers of Lulo cells were incubated with promastigotes and adhesion was assessed using both light microscopy and scanning electron microscopy. Findings. The results indicate that species from the subgenera Leishmania and Viannia have great potential to adhere to Lulo cells. The highest adherence rate was observed for L. (L.) chagasi after 24 h of incubation with Lulo cells (27.3 1.8% of cells with adhered promastigotes), followed by L. (L.) amazonensis (16.0 0.7%) and L. (V.) braziliensis (3.0 0.7%), both after 48 h. In the ultrastructural analysis, promastigote adherence was also assessed by scanning electron microscopy, showing that, for parasites from both subgenera, adhesion occurs by both the body and the flagellum. The interaction of Lulo cells with Leishmania (L.) chagasi showed the participation of cytoplasmic projections from the former closely associating the parasites with the cells. Conclusions: We present evidence that Lulo cells can be useful in studies of insect-parasite interactions for Leishmania species. © 2011 Côrtes et al; licensee BioMed Central Ltd.